2019
DOI: 10.3390/su11030679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Improvement Effect of Limestone Powder Waste in the Stabilization of Swelling Clayey Soil

Abstract: The natural stone industry generates large amounts of industrial waste every year. Limestone powder produced by the activity of this industry is dumped into landfills, generating an environmental impact that could be reduced by using this waste as a binder in building materials. In the present work, the use of this by-product as an addition for soil improvement of clayey soils has been studied. The tested natural soil is a soft clay from southeastern Spain, which has been mixed by adding 5, 10, 15, 20, and 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…The publication [30] reported that Compression Index and Swelling Index decreased up to 27% and 31%, respectively, when the soil was mixed with 25% of limestone powder. This addition decreases the compressibility of the soil as the slope of the virgin and rebound consolidation curves are reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The publication [30] reported that Compression Index and Swelling Index decreased up to 27% and 31%, respectively, when the soil was mixed with 25% of limestone powder. This addition decreases the compressibility of the soil as the slope of the virgin and rebound consolidation curves are reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fly ash has been shown to increase compressive strength and produce similar behavioral trends to Portland cement [11]. The use of limestone waste has been shown to reduce the swelling properties of soil, producing a more compact microstructure when examined using SEM imaging [21]. Milled brick debris has also been shown to improve the compressive strength of soils when tested using the unconfined compression test [22].…”
Section: Introductionmentioning
confidence: 99%
“…Other forms of industrial waste have been examined as potential soil improvement techniques [11,12,21,22]. Fly ash has shown the ability to reduce plastic strain in clay soils when exposed to freeze-thaw cycles [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the same research, the carbonation effect on the treated soil was also examined. In a work published earlier, Pastor et al [22] proved the ability of limestone/calcite to improve the swelling potential of clayey soils. Lime was observed to consistently improve the soil properties examined with increased proportion.…”
Section: Introductionmentioning
confidence: 99%